Strategi Bisnis Porter dan Dampaknya terhadap Kinerja Keuangan Sektor Perbankan di Bursa Efek Indonesia 2020 - 2025 - Mustanwir Zuhri; Adji Rizki Nashantyawarman (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study aims to analyze the effect of Porter’s business strategies on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The business strategies examined include cost leadership strategy measured by the operation expenses to operating income (BOPO) ratio, differentiation strategy proxied by Fee-Based Income (FBI) ratio, and focus strategy measured by the micro, small, and medium-sized enterprise (MSME-UMKM) credit ratio. Financial performance is represented by return on assets (ROA). This research adopts a quantitative approach using panel data regression, i.e. Random Effect Model (REM), which was determined as the best model. The results indicate that the BOPO ratio has a negative impact on ROA, implying that higher operational costs reduce profitability, while efficient cost management improves financial performance. FBI also shows a negative effect on ROA; however, the increase in differentiation services has not been fully balanced by effective maintenance cost management. The UMKM credit ratio has a positive impact on ROA, suggesting that the UMKM sector can contribute to profitability when supported by proper risk mitigation. Among the three strategies tested, cost leadership strategy is found to be the most dominant in influencing financial performance. This study indicates that business strategies in the banking sector are not merely theoretical concepts, but can be implemented simultaneously as long as one strategy remains dominant as the foundation of managerial decision-making.